Political Communication Through Social Media in the 2024 Enrekang Regional Election: Komunikasi Politik Melalui Media Sosial Pada Pilkada Enrekang Tahun 2024 - Fajar, Muhammad; Bakhtiar, Bakhtiar; Nur, Hasruddin (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Social media has become a major arena in contemporary political communication by expanding access to information, accelerating message circulation, and enabling direct interaction between political actors and citizens. Specific Background: In the 2024 local election context, this study examines how social media was used in local political communication, particularly through visual content, persuasive narratives, publication of campaign activities, and volunteer community accounts. Knowledge Gap: Although social media is widely used in electoral campaigns, its role in shaping voter interest and participation in a semi-urban local setting with strong communal relations remains insufficiently described. Aims: This study aims to analyze political communication strategies through social media and their relation to voter interest and voter participation in the 2024 local election. Results: The findings show that candidates used attractive visual content, leadership-centered persuasive narratives, vision-mission communication, campaign activity publication, and volunteer accounts to distribute political messages. Social media supported voter interest through easier information access, rapid message dissemination, and emotional closeness between candidates and voters. It also broadened political awareness, encouraged public discussion, motivated engagement in the electoral process, and simultaneously presented risks of disinformation and negative campaigning. Novelty: This study presents a contextual account of digital political communication in a semi-urban local setting where social media operates as a complementary instrument alongside direct social interaction and social legitimacy. Implications: The findings underline that local digital campaign practices should be aligned with social context, political credibility, and community communication patterns. Highlights• Attractive visual content and persuasive narratives expanded candidate visibility in digital political communication.• Easier information access and rapid message circulation increased voter interest during the local election.• Political awareness, public discussion, and electoral engagement grew alongside risks of disinformation. KeywordsPolitical Communication; Social Media; Political Visibility; Voter Interest; Voter Participation